Hubungan Penggunaan Laptop dengan Derajat Near Point Convergence Menggunakan Alat Royal Air Force Rule (RAF RULE) Pada Pegawai di Rumah Sakit Mata Makassar - nuralam; Ariyanie Nurtania; Hasnawati S (RS Mata Makassar, 2025)
This study aims to determine the relationship between laptop use and the degree of Near Point Convergence (NPC) among employees at the Makassar Eye Hospital in 2024 using the Royal Air Force Rule (RAF Rule) tool. The research uses a descriptive method with a cross-sectional approach involving 36 participants selected through purposive sampling. Data were analyzed using univariate and bivariate statistical tests. Results showed no significant relationship between NPC and age (p = 0.149) or gender (p = 0.480). However, a significant relationship was found between screen time and NPC (p = 0.035), suggesting that prolonged laptop use can negatively affect convergence ability. These findings underscore the need for awareness and preventive strategies among individuals with extended screen exposure to minimize risks of convergence insufficiency.